Kraj ili preporod kroatistike u Njemačkoj? - Krnić, Goran (Array, 2008)
Croatian language studies have as a result of the contemporary focus on intercultural pluralism, and above all because of the Croatia's political independence, made up for what it has lost with the reduction of the student population – building and raising awareness of its identity. Reforms are under way within academic Slavic languages studies in Germany that also have an influence on the status of Croatian language studies within German society. Interdisciplinary studies are gaining in importance, especially in market-profitable combinations. Croatian literature, language and culture are currently taught at fifteen German universities. Germany eagerly awaits the Leipzig Book Fair, whose partner country in 2008 is Croatia. Every spring the international fair in Leipzig pools Europe's publishing elite. Along with excellent writers from the homeland, Croatian authors from around the world will have an opportunity to make a joint appearance at this prestigious author's fair in the heart of Europe. The city of Leipzig, know as a centre of fairs and one of the key cultural hubs of both German and European history, lives every spring in the spirit of the slogan Leipzig Reads. In 2008 Leipzig reads Croatian! The success of the Croatian appearance in Leipzig will be a boost to the development of Croatian language studies in Germany and the desired ticket to the European culture scene. The author believes that a newly founded Croatian language studies association will contribute most to the development of Croatian language studies in Germany. The Deutsche Gesellschaft fuer Kroatistik (German Association for Croatian Language Studies) was established in 2007 as an association that aims to link all those in Germany professionally active in Croatian language and literature, and will serve as a platform for joint projects and as the umbrella partner for communication and cultural exchange with Croatia.